O uso de efluentes tratados de laticínio na fertirrigação - Mello, Adailton de (2022)
The state of Rio Grande do Sul has several industries that have effluent treatment systems, therefore, in the present work, those that are in the food sector are approached, more specifically in the dairy sector. These companies perform the treatment of effluents, soon after, emit them in the beds of streams and rivers. This course conclusion work had as main objective to evaluate the economic and environmental viability of the application of treated effluents through irrigation in an agricultural area at the county of Marau - RS. In this way, aspects of the area and the effluent treated with them were evaluated during this work, the maximum application rate was determined and later the cost of implantation and operation was budgeted, with its results, the investment payback. In view of this, it can be concluded that it is economically viable in the long term, taking about 15 years for the investment to pay off, denoting positive results regarding the pluviometry of the area, which favors the increase of productivity, avoiding water stress due to the lack of water to the plants, as well as the availability of nutrients for the implanted crops through fertirrigation. In terms of environmental viability, it is concluded that it will be very beneficial, as it will no longer emit an organic load of 0.61 tons per year in water bodies, avoiding possible damage to water bodies.